Logistics management in cement manufacturing industry: a case study of Seven Rings Cement in Bangladesh - Karim, Shahjadul (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.